Designing game applications or educative games to recite Al Qur'an based on interactive multimedia At the TPQ (Al Qur'an Learning Center) of Darussalam - Ipnuwati, Sri; Rohman, Khabibur; Mandala, Sri Surya (JTKSI (Jurnal Teknologi Komputer dan Sistem Informasi), 2024)
With technological developments, learning in schools or lectures can implement computer-based learning systems. With the presence of technology, the teaching process using educational game applications for reciting the Qur'an can be an alternative learning method when students feel bored or tired during learning. Reciting the Qur'an, which refers to the activity of reading the Qur'an, is a skill that every Muslim should have and that needs to be taught to children from an early age, starting before they enter school. This is an important part of forming their character. However, at an early age, children still tend to prefer playing, and limited methods of teaching the Koran may not be interesting enough for them. Therefore, an interactive learning method is needed using audio-visual aids, such as educational games. This approach not only makes learning more interesting but also more interactive. This application can increase children's understanding and knowledge about the Islamic religion, especially in terms of reciting the Qur'an. By applying the concept of learning while playing, children become more comfortable, interested, and happy in understanding and practicing the teachings of the Islamic religion.